Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/j.ijsu.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Is open surgery or endovascular therapy best to treat acute mesenteric occlusive disease?

Abstract: A best evidence topic in vascular surgery was written according to a structured protocol. The question addressed whether endovascular treatment improved peri-operative outcomes when compared to an open approach to restore arterial perfusion in acute mesenteric occlusive disease. Four hundred and ninety seven papers were identified using the reported search; of which 4 represented the best evidence to answer the question and are discussed. The evidence on this subject is limited, comprising largely of non-rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Few studies have shown that surgery followed by endovascular management would result in less bowel resection compared to direct open surgery. 12,13 The classic clinical scenario is a patient complaining of severe acute abdominal pain without any significant examination findings. 14 Other clinical presentations are nausea, vomiting, diarrhoea and bleeding per rectum.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have shown that surgery followed by endovascular management would result in less bowel resection compared to direct open surgery. 12,13 The classic clinical scenario is a patient complaining of severe acute abdominal pain without any significant examination findings. 14 Other clinical presentations are nausea, vomiting, diarrhoea and bleeding per rectum.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a few related studies reporting small sample sizes [ 8 – 12 , 19 , 20 ]. However, whether or not interventional therapy should be the primary treatment for ATOS is still controversial [ 14 , 15 ]. In this study, we reported the endovascular treatment outcomes of 18 patients with ATOS in China and showed that endovascular treatment exhibited advantages in the lower laparotomy requirement, shorter average length of bowel resection, and lower 30-day mortality compared with open surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last years, a few studies reported the employment of endovascular revascularization in the treatment of ATOS [ 8 – 12 ], with rapid blood supply reestablished and relatively small resultant trauma. It was shown by very few studies that endovascular treatment resulted in significantly less bowel resection and shorter bowel syndrome and mortality than open surgery [ 13 ]; however, whether or not endovascular interventional therapy should be the primary treatment for ATOS is still controversial [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…No randomized control trial has been performed to assess and compare open surgery to an endovascular approach, as patients with AMI are very heterogenic and physiologically different [ 97 ]. Much controversy surrounds the use of endovascular techniques as primary management of AMI [ 98 ]. Some studies report lesser need for laparotomy, less bowel resection, and significantly lower mortality rate with endovascular techniques compared to surgery [ 99 ].…”
Section: Pathophysiology and Epidemiologymentioning
confidence: 99%